Nitrogen reduction with supplemental irrigation enhances yield by delaying leaf senescence and optimizing grain-filling process for ridge-furrow film mulching winter wheat - Xiaobo Gu; Yang Xu; Tongtong Zhao; Yadan Du; Yuanling Zhang; Yuyu Tian; Zhikai Cheng; Huanjie Cai; Zhandong Liu (Agricultural Water Management)
The ridge-furrow film mulching (RFM) planting pattern has been extensively implemented in the arid regions of northwest China to improve grain yields. However, the optimal supplemental irrigation rate to further increase the yield of winter wheat under RFM remains unclear. Furthermore, excessive application of nitrogen fertilizer has resulted in severe resource inefficiency and environmental pollution. In order to determine the optimal combination of supplemental irrigation and nitrogen application rates for high-yielding winter wheat under RFM, a two-year (2022 −2024) field experiment was conducted to evaluate the effects of varying irrigation and nitrogen amounts on soil water content, chlorophyll content, aboveground dry matter, grain-filling process, yield, and water-nitrogen use efficiencies. The experiment comprised three supplemental irrigation rates (I0: 0 mm, I1: 30 mm, I2: 60 mm; which were applied at both overwintering and jointing stages), and four nitrogen application rates (N0: 0 kg N ha−1, N1: 100 kg N ha−1, N2: 200 kg N ha−1, and N3: 300 kg N ha−1), with a local conventional field management (flat planting without mulching combination with 60 mm irrigation at both overwintering and jointing stages, and 300 kg N ha⁻1) as the control (CK). Compared to CK, I1N2 increased the soil water content by 2.90 % in the 0 −100 cm soil layer throughout the winter wheat growth seasons. The relative leaf chlorophyll content (SPAD) decreased from top to bottom layers, and showed an upward trend with the increase of irrigation and nitrogen levels. The leaf area index at heading stage and aboveground biomass at maturity stage were maximized in I1N2, with significant increases of 7.62 %−89.94 % and 5.71 %−62.38 % compared to other treatments. The active grain-filling period in I1 and I2 was extended by 0.46 −2.44 days and 0.97 −2.38 days compared to I0. In both two years, the I1N2 achieved the greatest grain yield (9423.89 kg ha−1) and water use efficiency (WUE) (26.65 kg ha−1 mm−1), with a relative greater nitrogen partial factor productivity (NPFP) of 47.12 kg kg−1. By conducting a comprehensive evaluation of grain yield, WUE, and NPFP, the combination of 55.8 −66.1 mm supplemental irrigation and 135.0 −147.2 kg N ha−1 nitrogen application was recommended for winter wheat under RFM to obtain high yield and high water-nitrogen use efficiencies. The results of present study would provide theoretical support and technical guidance for enhancing sustainable agriculture development in arid regions of northwest China.